2005
DOI: 10.1097/00001199-200509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Community Integration Status 4 Years After Traumatic Brain Injury

Abstract: For research purposes, proxy data are acceptable but clinicians should assess outcomes and set goals with input from both persons with TBIs and their proxies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Findings here are mixed. While some investigations have shown greater agreement for spouse surrogates than for other relatives or friends, 22 other have failed to obtain this finding. 21 Hart and colleagues 17 found that more frequent contact resulted in greater agreement, whereas Sander and colleagues 19 did not find this association.…”
Section: Use Of Surrogate Informantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Findings here are mixed. While some investigations have shown greater agreement for spouse surrogates than for other relatives or friends, 22 other have failed to obtain this finding. 21 Hart and colleagues 17 found that more frequent contact resulted in greater agreement, whereas Sander and colleagues 19 did not find this association.…”
Section: Use Of Surrogate Informantsmentioning
confidence: 97%
“…However, previous investigations have also shown that agreement between the person with brain injury and a surrogate informant is mediated by injury severity such that there is greater agreement when injury is milder. 19,22 Thus, persons with the most severe injuries are most likely to report fewer problems and have poorer agreement with informants. For these patients, it can be argued that surrogate report for relatively objective outcomes such as degree of cognitive impairment or neurobehavioral disturbance may be more accurate than self-report by the person with injury though, again, this argument does not apply to more subjective judgments such as overall satisfaction with life.…”
Section: Use Of Surrogate Informantsmentioning
confidence: 99%
“…En lo referente al impacto en la participación ocupacional (PO) en personas con DCA, en dos investigaciones, se ha concluido que la PO es limitada o se discontinua, evidenciando cambios más significativos en las personas con daños moderado y severo (Bascones Serrano en López Polonio 2010 ; Dawson, Markowitz, Stuss, 2005).…”
Section: Uso De Cinturón De Seguridadunclassified
“…Estos datos son coincidentes con Bascones Serrano (2010), Dawson et al, (2005), Sendroy-Terrill et al (2010) y (Barbieri et al, (2010). Todas las personas con DCA presentaron mejorías en el grado de autonomía en la PO en las AVD entre el ingreso a la internación y el seguimiento, sin embargo a los tres meses ninguno alcanzaba el grado de PO en AVD que tenía antes de la lesión cerebral adquirida.…”
Section: Participación De Las Personas Con Dcaunclassified
“…Successful community reintegration is commonly identified as a primary goal of rehabilitation programmes for individuals with acquired brain injury (ABI) [1][2][3]. However, despite the emphasis placed upon community reintegration by rehabilitation service providers, many individuals with ABI continue to experience difficulties in managing the impact of injury-related deficits and the loss of meaningful life roles during the transition from hospital to home [4].…”
Section: Introductionmentioning
confidence: 99%